2020
DOI: 10.1101/2020.12.10.420711
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Cell type-specific biogenesis of novel vesicles containing viral products in human cytomegalovirus infection

Abstract: Human cytomegalovirus (HCMV), while highly restricted for the human species, infects an unlimited array of cell types in the host. Patterns of infection are dictated by the cell type infected, but cell type-specific factors and how they impact tropism for specific cell types is poorly understood. Previous studies in primary endothelial cells showed that HCMV infection induces large multivesicular-like bodies that incorporate viral products including dense bodies and virions. Here we define the nature of these … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
6
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 82 publications
1
6
0
Order By: Relevance
“…While investigating the provenance of these MViBs, we also found that they carry CD63, which is also present at the release events. The presence of CD63 potentially links MViBs to the endosomal/exosomal pathway, which would be in line with earlier studies, which reported multivesicular structures filled with HCMV virions (Bughio et al, 2013; Fraile‐Ramos et al, 2007, 2010; Momtaz et al, 2021; Schauflinger et al, 2011; Severi et al, 1988). However, in our hands, the MVB inhibiting drug U18666A does not inhibit EVA generation, which indicates that the properties of MViBs are different from classical cellular MVBs.…”
Section: Hcmv Uses Mvibs For Intermittent Bulk Release Of Virus Parti...supporting
confidence: 85%
See 2 more Smart Citations
“…While investigating the provenance of these MViBs, we also found that they carry CD63, which is also present at the release events. The presence of CD63 potentially links MViBs to the endosomal/exosomal pathway, which would be in line with earlier studies, which reported multivesicular structures filled with HCMV virions (Bughio et al, 2013; Fraile‐Ramos et al, 2007, 2010; Momtaz et al, 2021; Schauflinger et al, 2011; Severi et al, 1988). However, in our hands, the MVB inhibiting drug U18666A does not inhibit EVA generation, which indicates that the properties of MViBs are different from classical cellular MVBs.…”
Section: Hcmv Uses Mvibs For Intermittent Bulk Release Of Virus Parti...supporting
confidence: 85%
“…Although current data (Read et al, 2019; Schauflinger et al, 2013; Shaga Devan et al, 2021; Taisne et al, 2019) have mainly described that HCMV capsids individually bud into small vesicles in the AC (Figure 1a,b), several studies have described large vesicles filled with virus particles (Bughio et al, 2013; Fraile‐Ramos et al, 2010; Momtaz et al, 2021; Schauflinger et al, 2011; Severi et al, 1988). However, the relevance of these structures has remained unclear.…”
Section: Hcmv Uses Mvibs For Intermittent Bulk Release Of Virus Parti...mentioning
confidence: 98%
See 1 more Smart Citation
“…What is still unclear is why RhCMV vector-mediated MHC-II-restricted CD8 + T cell priming would be restricted to this cell type, as intrinsic MHC-II processing occurs in many cell types, including professional Agpresenting cells and non-Ag-presenting cells (36). It is possible that aspects of CMV infection in endothelial cells that differ from other viral target cells contribute an essential element of this priming mechanism (43)(44)(45).…”
Section: Discussionmentioning
confidence: 99%
“…It is plausible to hypothesize that these virus populations might undergo different envelopment processes in the cell and are exocytosed with a different spatiotemporal profile (Scrivano et al, 2011). While this manuscript was in preparation, a study from the Wilson and Goodrum lab suggested that virus-containing MVBs in fibroblasts and endothelial cells are derived from different cellular membranes, which would add another potential HCMV egress pathway that could result in different virus populations; however, it is unclear if these pathways are functional in egress (Momtaz et al, 2021).…”
Section: Discussionmentioning
confidence: 99%